PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PT PHILIA CITRA SEJAHTERA PALEMBANG - Ismandra (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
Motivation is a factor that drives a person to do a certain activity, motivation is often interpreted as a factor driving a person's behavior. The study looked at how the influence of motivation on the performance of employees of PT. Philia Citra Sejahtera Palembang uses simple linear regression analysis techniques. The results showed that work motivation is very significant and positive influence on the performance of employees of PT Philia Citra Sejahtera palembang. This is evidenced from the results of the determination coefficient calculation which is equal to 75.2%.